АЛИШЕР НАВОИЙ ФЕНОМЕНИ ВА ЖАДИД АДАБИЁТИ НАМОЯНДАЛАРИ (Scientific journal of the Fergana State University, 2023)
In this article unlimited love of djadids to the great poet A.Navoi, whose creative work they consider as a model to imitate, is described.